Associations between factors related to work and health and the experience of climacteric symptoms: A study among 52–56-year-old full-time working Finnish women before any treatment for the symptoms - Lipasti, Maija; Jalava-Broman, Jaana; Sillanmäki, Lauri; Mäkinen, Juha; Rautava, Päivi (Elsevier B.V., 2025)
Objectives: To examine associations between factors related to work and health and the experience of climacteric symptoms among middle-aged full-time working Finnish women before receiving any treatment for the symptoms.
Methods: A cross-sectional study among Finnish women aged 52-56 years who were full-time employed and had never used any treatment for the studied symptoms (n = 313). The experience of symptoms was assessed as the occurrence and severity of menopause-related symptoms that have a negative impact on women's general wellbeing or wellbeing at work. These are hot flushes, sweats, sleeping problems, vaginal dryness and tenderness, loss of sexual desire, and depressive symptoms. The studied work- and health-related factors were the experience of the psychosocial work environment, health behaviors (body size, physical activity, and smoking habits), perceived stress and perceived social support.
Results: A high-strain job, smoking, increased levels of stress, and low levels of social support were associated with both the occurrence and severity of the studied symptoms. Women with these traits experienced symptoms more often and more severe than women without these traits.
Conclusions: Several factors may be in association with how a full-time working woman experience climacteric symptoms before receiving any treatment for them. Therefore, the health and wellbeing of middle-aged working women should be considered in all aspects including climacteric symptoms, both expressed and hidden, the work environment, health behaviors, perceived stress and perceived social support. Any healthcare professional should be aware of this. Furthermore, healthcare professionals and employers should work closely together to promote and improve women's health and wellbeing.